PDE10A Mutation as an Emerging Cause of Childhood-Onset Hyperkinetic Movement Disorders: A Review of All Published Cases - Kalampokini, Stefania; Xiromerisiou, Georgia; Bargiotas, Panagiotis; Anastasiadou, Violetta Christophidou; Costeas, Paul; Hadjigeorgiou, Georgios M. (Neuropediatrics, 2024)
Cyclic nucleotide phosphodiesterase (PDE) enzymes catalyze the breakdown of cyclic adenosine monophosphate (cAMP) and cyclic guanosine monophosphate (cGMP), which act as intracellular second messengers for signal transduction pathways and modulate various processes in the central nervous system. Recent discoveries that mutations in genes encoding different PDEs, including PDE10A, are responsible for rare forms of chorea in children led to the recognition of an emerging role of PDEs in the field of pediatric movement disorders. A comprehensive literature review of all reported cases of PDE10A mutations in PubMed and Web of Science was performed in English. We included eight studies, describing 31 patients harboring a PDE10A mutation and exhibiting a hyperkinetic movement disorder with onset in infancy or childhood. Mutations in both GAF-A, GAF-B regulatory domains and outside the GAF domains of the PDE10A gene have been reported to cause hyperkinetic movement disorders. In general, patients with homozygous mutations in either GAF-A domain of PDE10A present with a more severe phenotype and at an earlier age but without any extensive abnormalities of the striata compared with patients with dominant variants in GAF-B domain, indicating that dominant and recessive mutations have different pathogenic mechanisms. PDE10A plays a key role in regulating control of striato-cortical movement. Comprehension of the molecular mechanisms within the cAMP and cGMP signaling systems caused by PDE10A mutations may inform novel therapeutic strategies that could alleviate symptoms in young patients affected by these rare movement disorders.
Keywords: PDE10A mutation; hyperkinetic movement disorder; chorea; children; pediatric